-5=g-5

Simple and best practice solution for -5=g-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5=g-5 equation:


Simplifying
-5 = g + -5

Reorder the terms:
-5 = -5 + g

Add '5' to each side of the equation.
-5 + 5 = -5 + 5 + g

Combine like terms: -5 + 5 = 0
0 = -5 + 5 + g

Combine like terms: -5 + 5 = 0
0 = 0 + g
0 = g

Solving
0 = g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-1g' to each side of the equation.
0 + -1g = g + -1g
Remove the zero:
-1g = g + -1g

Combine like terms: g + -1g = 0
-1g = 0

Divide each side by '-1'.
g = 0

Simplifying
g = 0

See similar equations:

| -3x-7=2x+3 | | 5n-6n= | | -10p^2/3125-5p^2 | | -73+11y+9=4(4y-4)-8 | | -48=6(y+1) | | -7x+22=22 | | X^2-4x-44=-4 | | p-5(1-p)=-10p+(1-p) | | (x+2y)*dx+y*dy=0 | | N^2-12n-56=-8 | | 5x-3=3*(x+7)+3x | | q+10(1-q)=-5q+(1-q) | | 5(c-4)+3=2+c-19 | | q+(1-q)=-5q+(1-q) | | .6x-.2(10-3x)=-.4x-7 | | 9(w-5)=27 | | 18=-8x+66 | | 1+p=2p-1 | | 64v^3-t^3= | | 64ft^3-t^3= | | 4x^3+6x^2+1=0 | | p-10(1-p)=-5p+(1-p) | | 7p+2=6p-6 | | 17=-5b+2 | | 41=7n-8 | | 22=-4n+6 | | 10u+9=59 | | -6j+5=47 | | -5r+4=49 | | 6w-7=-25 | | -14=-3y+7 | | 3y+15=-y-13 |

Equations solver categories